2019
DOI: 10.3389/fpls.2019.00210
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Silica and Biopolymer Structural Components in the Spore Elater of Equisetum arvense, an Ancient Silicifying Plant

Abstract: Equisetum species are primitive vascular plants that benefit from the biogenesis of silica bio-organic inclusions in their tissues and participate in the annual biosilica turnover in local eco-systems. As means of Equisetum reproduction and propagation, spores are expected to reflect the evolutionary adaptation of the plants to the climatic conditions at different times of the year. Combining methods of Raman and scanning electron microscopy and assisted with density functional theory, we conducted material sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…biology [51]. Indeed, comparing our experimental and theoretical studies [26], a lignin-like component is likely to contribute into Raman activities at 1606 and 1700 cm -1 . In Supplementary information Fig.…”
Section: Interpretation and Spectral Assignmentsmentioning
confidence: 65%
See 2 more Smart Citations
“…biology [51]. Indeed, comparing our experimental and theoretical studies [26], a lignin-like component is likely to contribute into Raman activities at 1606 and 1700 cm -1 . In Supplementary information Fig.…”
Section: Interpretation and Spectral Assignmentsmentioning
confidence: 65%
“…Furthermore, Alternaria group is known to exhibit active lignin biochemistry [51]. In this contribution we used the results of our theoretical studies on a lignin-like structural segment reported previously [26].…”
Section: Model Molecular Systems For Theoretical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have moved beyond the above‐mentioned microscopy techniques to gain additional insights into gametophyte dispersal. The combination of SEM with chemical spectral techniques displays the distribution of elements and polymers involved in spore dispersal in the horsetail Equisetum (Volkov et al, 2019 ). 3D images can be obtained using X‐ray computed tomography and used to further understand soft tissue structure (Staedler et al, 2013 ).…”
Section: Microscopy and Ultrastructurementioning
confidence: 99%
“…Capsule walls and dehiscence grooves (Duckett and Pressel, 2019), arrangement of organs (Taylor et al, 2006;Whitaker et al, 2007;Zhang et al, 2020), water-absorbing potential (Taylor et al, 2006;Zhang et al, 2020), cavitation and gas bubbles (Hovenkamp et al, 2009;Poppinga et al, 2015) SEM Ultrastructure of surfaces (spores, dispersal organs, etc.) ~1,000,000× Standard or cryopreservation, environmental conditions Characteristics of diaspores (Pohjamo et al, 2006;Hovenkamp et al, 2009;Poppinga et al, 2015;Zanatta et al, 2016;Gómez-Noguez et al, 2017), sporophyte dispersal organs (Hovenkamp et al, 2009;Poppinga et al, 2015;Duckett and Pressel, 2019;Zhang et al, 2020), mechanism (Hovenkamp et al, 2009;Poppinga et al, 2015;Duckett and Pressel, 2019), elemental analysis (Volkov et al, 2019) TEM Subcellular structures ~2,000,000×…”
Section: -1000×mentioning
confidence: 99%